2008
DOI: 10.1111/j.1542-474x.2007.00194.x
|View full text |Cite
|
Sign up to set email alerts
|

P‐Wave Duration and Dispersion in Obese Subjects

Abstract: Our data suggest that obesity affects P-wave dispersion and duration, and changes in P dispersion may be closely related to the clinical and the echocardiographic parameters such as BMI, LAD, IVST, LVPWT, and LVM.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
48
0
3

Year Published

2009
2009
2022
2022

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 57 publications
(55 citation statements)
references
References 26 publications
4
48
0
3
Order By: Relevance
“…This increase in duration with increasing adiposity is consistent with prior smaller data sets, 7,10-12 and others have reported increased P wave durations and left atrial sizes by echocardiography when obese subjects were compared to age-and sex-matched controls. 10,11 It is possible the increased duration demonstrated here may be a manifestation of left atrial enlargement directly related to obesity, as secondarily associated disease states (e.g., systemic hypertension, diabetes mellitus, and coronary artery disease) are unlikely to have developed yet in this young cohort.…”
Section: Discussionmentioning
confidence: 92%
“…This increase in duration with increasing adiposity is consistent with prior smaller data sets, 7,10-12 and others have reported increased P wave durations and left atrial sizes by echocardiography when obese subjects were compared to age-and sex-matched controls. 10,11 It is possible the increased duration demonstrated here may be a manifestation of left atrial enlargement directly related to obesity, as secondarily associated disease states (e.g., systemic hypertension, diabetes mellitus, and coronary artery disease) are unlikely to have developed yet in this young cohort.…”
Section: Discussionmentioning
confidence: 92%
“…Obesity increases the risk of developing AF by 49% in the general population, and the risk escalates in parallel with increased body mass index. 36 Kosar et al 37 reported that obesity affected PWD and changes in PWD were closely related to body mass index. Left atrium size was correlated with PWD, as expected.…”
Section: Resultsmentioning
confidence: 99%
“…P-wave dispersion is thought to reflect 'discontinuous and inhomogeneous propagation of sinus impulses and prolongation of atrial conduction time' [18].…”
Section: Mechanisms Of How Obesity and Obstructive Sleep Apnea Increamentioning
confidence: 99%